Clinical Efficacy of Cycloferon in The Complex Therapy of Tuberculosis: Systematic Review and Meta-Analysis Results - N. K. Mazina; P. V. Mazin; R. KH. Khafizyanova (Антибиотики и Химиотерапия, 2020)
The generalized assessment of cycloferon immunologic modulator efficacy was carried out to estimate its' therapeutic potency as an adjuvant as a part of basic therapy of pulmonary tuberculosis. Heterogeneity of comparison groups and variability of therapeutic response indicators was taken into account. Nine publications formed the basis of the systematic overview and meta-analysis after being extracted from an array of scientific literary data (531 scientific publications on clinical performance of cycloferon drug). The values of the formalized indicators of cycloferon clinical efficacy (increase in absolute and relative benefits, odds ratio, NNT, etc.) were calculated. Efficacy parameters varied in different randomized clinical trials, but this variability was leveled by uniform design and symmetry of the comparison groups to allow the results interpretation as a reflection of real clinical practice. It is shown that the use of cycloferon to enhance immunogenesis in pharmacotherapy of tuberculosis increases rapid recovery rate by more than 2.7 times and decreases the likelihood of adverse effects.